1992
DOI: 10.1007/bf00128130
|View full text |Cite
|
Sign up to set email alerts
|

Subspace methods for recovering rigid motion I: Algorithm and implementation

Abstract: As an observer moves and explores the environment, the visual stimulation in his/her eye is constantly changing. Somehow he/she is able to perceive the spatial layout of the scene, and to discern his/her movement through space. Computational vision researchers have been trying to solve this problem for a number of years with only limited success. It is a difficult problem to solve because the optical flow field is nonlinearly related to the 3D motion and depth parameters.Here, we show that the nonlinear equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
244
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(247 citation statements)
references
References 58 publications
2
244
0
1
Order By: Relevance
“…Several of these alternative approaches are compared to the computational mechanisms in the STARS model. Heeger and Jepson (1992) produced an influential mathematical analysis on the recovery of the components of optic flow, namely translation, rotation, and depth, from a set of discrete samples. Their subspace algorithm sets up a least-squares optimization problem that solves for the components of the flow field, without the use of explicit extraretinal information, although psychophysical studies have shown that extraretinal signals are required for accurate heading perception during sufficiently fast eye rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these alternative approaches are compared to the computational mechanisms in the STARS model. Heeger and Jepson (1992) produced an influential mathematical analysis on the recovery of the components of optic flow, namely translation, rotation, and depth, from a set of discrete samples. Their subspace algorithm sets up a least-squares optimization problem that solves for the components of the flow field, without the use of explicit extraretinal information, although psychophysical studies have shown that extraretinal signals are required for accurate heading perception during sufficiently fast eye rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Hegger and Jepson estimator: Hegger and Jepson proposed the so-called linear subspace method [24,25]. Given the optical ow of a set of n image points, the following relationship can be formulated:…”
Section: Methods Directly Based On the Optical Owmentioning
confidence: 99%
“…Due to its importance, many algorithms dealing with the problem of estimating egomotion have appeared in the literature. The following paragraphs provide a short review of a few representative methods; more detailed discussions can be found in [7,8,10]. Most of the methods reviewed here rely on the availability of a dense optical flow field to describe 2D motion.…”
Section: Introductionmentioning
confidence: 99%
“…Heeger and Jepson [7] also make use of the residual function introduced in [1] and propose an efficient search technique for locating its minimum. Hummel and Sundareswaran [8] present an algorithm for finding the rotational motion and one for locating the FOE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation